A systematic review on reporting outcomes and outcome measures in trials on synthetic mesh procedures for pelvic organ prolapse: Urgent action is needed to improve quality of research. Issue 2 (15th November 2018) - de Mattos Lourenco, Thais R.; Pergialiotis, Vasilis; Duffy, James M. N.; Durnea, Constantin; Elfituri, Abdullatif; Haddad, Jorge M.; Betschart, Cornelia; Falconi, Gabriele; Doumouchtsis, Stergios K.; ,
Abstract : The use of synthetic mesh in pelvic organ prolapse surgery is being closely scrutinized because of serious concerns regarding life‐changing complications such as erosion, pain, infection, bleeding, dyspareunia, organ perforation, and urinary problems. Randomized trials and their syntheses in meta‐analysis offer a unique opportunity to assess efficacy and safety. However, outcomes and outcome measures need to be consistently selected, collected, and reported across randomized trials to be effectively combined in systematic reviews. Aims: We evaluated outcome and outcome measure reporting across randomized controlled trials on surgical interventions using synthetic mesh for pelvic organ prolapse. Methods: Systematic review of randomized controlled trials using synthetic mesh for the treatment of pelvic organ prolapse. The selected studies were evaluated using Jadad and MOMENT criteria. Outcomes and outcome measures were systematically identified and categorized. Results: Seventy‐one randomized trials were included. Twenty‐four different types of mesh were identified. Included trials reported 110 different outcomes and 60 outcome measures. Erosion (40 trials, 78%), pain (29 trials, 56%), bleeding (31 trials, 61%), and dyspareunia (25 trials, 49%) were the most frequently reported outcomes. The longest follow up was 74 months. Conclusions: Most randomized trials evaluating surgical interventions using synthetic mesh for pelvic organ prolapse failed to report on clinically important outcomes and to evaluate efficacy and safety over the medium‐ and long‐term. Developing and implementing a minimum data set, known as a core outcome set, in future vaginal prolapse trials could help address these issues.